For #1 we’re adding/subtracting/multi polynomials I need the answer for #1 its kind of shaded off
1 answer:
Answer:
- 6x² - 2x + 1
Step-by-step explanation:
Given
(2x³ - 4x² - 3x + 5) + (- 2x³ - 2x² + x - 4)
Both parenthesis are distributed by 1 thus just remove them
= 2x³ - 4x² - 3x + 5 - 2x³ - 2x² + x - 4 ← collect like terms
= - 6x² - 2x + 1
You might be interested in
Step-by-step explanation:
focus(p) is on the x axis= -1
vertex=(0,0)
parabola equation----- (y-h)^2 =4p(x-k)
(h, k)=(0,0)
(y-0)^2 =4(-1)(x-0)
|
|
|
y^2 = -4x
that is the answer
Answer:
x=66°
Step-by-step explanation:
48+x+x=180
2x=180-48
2x=132
x=132/2=66
Answer:
Step-by-step explanation:
1.) -15.9, -15.2, -3.6, 3.6
2.) second one is already correct
3.)-2.3, -2.03, 2.03, 3.0
Kevin is incorrect because x+x is adding two numbers, but x^2 is multiply.